Influence of residual achromatic aberration on the isochronicity in the FAIR collector ring. (26th November 2015) - Litvinov, S; Dolinskii, A; Koop, I; Weick, H
Abstract: In order to understand how the heavy elements from iron to uranium were produced in nature, masses and lifetimes of extremely exotic nuclei up to the limits of nuclear existence have to be measured. In particular, for modeling the r-process nucleosynthesis the nuclei close to the neutron drip line are relevant. However, such nuclei typically have very short half-lives and furthermore have tiny production cross-sections. The Super-FRS-CR facility at FAIR [1 ] offers unique possibilities for such measurements. Exotic nuclei with half-lives of will be produced and selected in flight with the Super-FRS fragment separator [2 ], injected and stored in the large acceptance collector ring (CR) [3 ] which will be tuned into the isochronous ion-optical mode and operated as a time-of-flight (TOF) spectrometer. We demonstrate here, a comparison between the achromatic and non-achromatic isochronous optics. The importance of the TOF detectors installation in the dispersion free region will be shown.